The effect of vocational rehabilitation on the employment outcomes of disability insurance beneficiaries: New evidence from Canada - Michele Campolieti; Morley K. L. Gunderson; Jeffrey A. Smith (IZA Journal of Labor Policy, 2014)
We estimate the effects of the vocational rehabilitation (VR) program run by the Canada Pension Plan Disability Program using administrative data. Identification relies on "selection on observed variables" plus careful comparison group selection and institutional knowledge regarding sources of conditional variation in participation. We employ several matching and weighting estimators and emphasize flexible conditioning on variables suggested by theory, the institutional setup and the literature. We find modest, and imprecisely estimated, impacts on employment outcomes for men and larger, sometimes statistically significant, impacts for women. A formal sensitivity analysis finds our results are quite robust to lingering selection on unobserved variables.
Keywords: I38; J08; J24; 330; Vocational rehabilitation; Disability; Evaluation; Matching